ANALYSIS OF THE EFFECT OF USER-GENERATED CONTENT (UCG) INFORMATION FROM SOCIAL MEDIA AND POSITIVE ELECTRONIC WORD OF MOUTH (E-WOM POSITIVE) ON TOURIST VISITING INTENTIONS IN INDONESIA: Keywords: Electronic Word of Mouth (e-Wom); Elaboration Likelihood Model (ELM); Social media; Travel intentions; User-Generated Content (UCG) - Femmy Effendy; Asep Samsul Bakhri (Master of Management, Mataram University, 2022)
This study aims to determine the role of user-generated content in social networks using the variables of information quality and credibility of information and e-WOM through receiving information in increasing the intention of visiting tourist destinations in Indonesia. This research was conducted quantitatively descriptive and verification. Data were collected by survey through online questionnaire using a differential semantic scale. Sampling technique with purposive sampling technique and distributing questionnaires randomly to respondents. Printed and electronic books, journals, and the internet as secondary data that support this research. A total of 112 samples were obtained, but only 85 samples that met the requirements for processing. Data processing with Smart PLS software or partial least squares (PLS) structural equation model (SEM), which aims to test the hypothesis of the influence between the variables of information quality, information credibility and e-WOM on information acceptance and travel intentions. The results of the research analysis show that the quality of information received by potential visitors has a very significant effect on how visitors adopt information and affects the intention to visit tourists in a tourist area, while the credibility of information does not affect how visitors adopt information as well as E-WOM Positive does not. influence the intention to visit tourists. This finding is expected to provide an illustration that the quality of information is the most influencing factor in the intention to visit tourists, so that relevant, accurate and up-to-date information is something that must be considered regarding tourist destinations, so that stakeholders can use influencers or appropriate reviews so that they can increase the potential number of tourists according to the expected target.